2014
DOI: 10.1007/s40037-014-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the initiation of the physician’s professional identity: Cornell’s urban semester program

Abstract: Calling for major reform in medical education, the Carnegie Institute report ‘Educating Physicians’ espoused the importance of assisting student trainees in forming their professional identities. Here, we consider the question: At what educational stage should future physicians begin this process? The literature suggests that the process begins when students matriculate in medical school; we posit, however, that premedical students can begin their proto-professional development as college undergraduates. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Following a review of the literature, we identified 8 model programs supporting university premedical students pursuing a career in medicine ( Table 1 ). [ 24–31 ] Though each of these programs aims to provide an opportunity for students to gain clinical exposure through physician shadowing, few integrate opportunities for reflection into the observership experience. For example, of these 8 programs, we found that only the Cornell University urban semester program, the Health Frontiers in Tijuana Undergraduate Internship Program at the University of California, San Diego, and the Stanford Immersion in Medicine Series incorporate opportunities for structured reflection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a review of the literature, we identified 8 model programs supporting university premedical students pursuing a career in medicine ( Table 1 ). [ 24–31 ] Though each of these programs aims to provide an opportunity for students to gain clinical exposure through physician shadowing, few integrate opportunities for reflection into the observership experience. For example, of these 8 programs, we found that only the Cornell University urban semester program, the Health Frontiers in Tijuana Undergraduate Internship Program at the University of California, San Diego, and the Stanford Immersion in Medicine Series incorporate opportunities for structured reflection.…”
Section: Introductionmentioning
confidence: 99%
“…Following a review of the literature, we identified 8 model programs supporting university premedical students pursuing a career in medicine (Table 1). [24][25][26][27][28][29][30][31] Though each of these programs aims to provide an opportunity for students to gain clinical exposure through physician shadowing, few integrate opportunities for reflection into the observership experience. For example, of these 8 [32].…”
Section: Introductionmentioning
confidence: 99%
“…Shadowing is used successfully in teaching nurses (Paskiewicz, 2002; Seldomridge, 2004; Porter et al ., 2009) and medical students (Spencer, 2003; Stalmeijer et al ., 2009; Jain et al ., 2012; Goldstein et al ., 2014, Micallef and Straw, 2014). Some authors name shadowing, among other methods, both as an instrument for training NMMs (Watkins et al ., 2014; Edmonstone, 2013; Edmonstone, 2011a; Skytt et al ., 2011) and as a technique for clinical leadership development (Enterkin et al ., 2013; Edmonstone, 2011b; Crethar et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is an important part of nurturing professionalism within medical students [5,6] and is related to how strongly individuals identify with their chosen professions. Some scholars also pay attention to the formation and factors that in uence medical students' professional identity [7][8][9][10]. For physicians-in-training, preliminary data suggest that good virtues in medical practice are associated with having a strong sense of professional identity [11].…”
mentioning
confidence: 99%